Targeting mechanoresponsive proteins in pancreatic cancer: 4-hydroxyacetophenone blocks dissemination and invasion by activating MYH14 - Surcel, Alexandra; Schiffhauer, Eric S.; Thomas, Dustin G.; Zhu, Qingfeng; Dinapoli, Kathleen T.; Herbig, Maik; Otto, Oliver; West-Foyle, Hoku; Jacobi, Angela; Kraeter, Martin; Plak, Katarzyna; Guck, Jochen; et al. (Cancer Research, 2019)
Metastasis is complex, involving multiple genetic, epigenetic, biochemical, and physical changes in the cancer cell and its microenvironment. Cells with metastatic potential are often characterized by altered cellular contractility and deformability, lending them the flexibility to disseminate and navigate through different microenvironments. We demonstrate that mechanoresponsiveness is a hallmark of pancreatic cancer cells. Key mechanoresponsive proteins, those that accumulate in response to mechanical stress, specifically nonmuscle myosin IIA (MYH9) and IIC (MYH14), a-actinin 4, and filamin B, were highly expressed in pancreatic cancer as compared with healthy ductal epithelia. Their less responsive sister paralogs—myosin IIB (MYH10), a-actinin 1, and filamin A—had lower expression differential or disappeared with cancer progression. We demonstrate that proteins whose cellular contributions are often overlooked because of their low abundance can have profound impact on cell architecture, behavior, and mechanics. Here, the low abundant protein MYH14 promoted metastatic behavior and could be exploited with 4-hydroxyaceto-phenone (4-HAP), which increased MYH14 assembly, stiffening cells. As a result, 4-HAP decreased dissemination, induced cortical actin belts in spheroids, and slowed retrograde actin flow. 4-HAP also reduced liver metastases in human pancreatic cancer-bearing nude mice. Thus, increasing MYH14 assembly overwhelms the ability of cells to polarize and invade, suggesting targeting the mechanoresponsive proteins of the actin cytoskeleton as a new strategy to improve the survival of patients with pancreatic cancer. Significance: This study demonstrates that mechanoresponsive proteins become upregulated with pancreatic cancer progression and that this system of proteins can be pharma-cologically targeted to inhibit the metastatic potential of pancreatic cancer cells.
CRIS-Team Scopus Importer:2022-08-05